Data science & big data analytics discovering, analyzing, visualizing and presenting data. (Wiley, 2014)
This book is about harnessing the power of data for new insights. The book covers the breadth of activities, methods, and tools that data scientists use. The content focuses on concepts, principles and practical applications that are relevant to any industry and technology environment.-- From publisher's description.